2016
DOI: 10.1016/j.eururo.2015.06.005
|View full text |Cite
|
Sign up to set email alerts
|

Relationship Between Prebiopsy Multiparametric Magnetic Resonance Imaging (MRI), Biopsy Indication, and MRI-ultrasound Fusion–targeted Prostate Biopsy Outcomes

Abstract: BACKGROUND Increasing evidence supports the use of MRI-ultrasound fusion-targeted prostate biopsy (MRF-TB) to improve the detection of clinically significant prostate cancer (PCa) while limiting detection of indolent disease compared to systematic 12-core biopsy (SB). OBJECTIVE We report results of MRF-TB and SB and the relationship between biopsy outcomes and pre-biopsy MRI in 601 men presenting to our center. DESIGN/SETTING/PARTICIPANTS Retrospective analysis of a prospectively acquired cohort of men pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
108
1
3

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 173 publications
(115 citation statements)
references
References 20 publications
3
108
1
3
Order By: Relevance
“…However, compared to the traditional TRUS-guided 12-core prostate biopsy, many studies showed that the 3D-Tb might have better sensitivity without statistical differences [14][15][16][17][18]. Furthermore, some researches showed that 3D-Tb tended to find more high-Gleasonscore (≥7) cases [16][17][18], but some other studies did not obtain significant results [14,15,[19][20][21][22]. To our knowledge, rarely do studies test the efficiency of 3D-Tb combined with Sb as primary endpoint.…”
Section: Introductionmentioning
confidence: 92%
“…However, compared to the traditional TRUS-guided 12-core prostate biopsy, many studies showed that the 3D-Tb might have better sensitivity without statistical differences [14][15][16][17][18]. Furthermore, some researches showed that 3D-Tb tended to find more high-Gleasonscore (≥7) cases [16][17][18], but some other studies did not obtain significant results [14,15,[19][20][21][22]. To our knowledge, rarely do studies test the efficiency of 3D-Tb combined with Sb as primary endpoint.…”
Section: Introductionmentioning
confidence: 92%
“…It has resulted in high cancer detection rates of >60% in correlation with the findings on mpMRI and has good prediction of tumour aggressiveness [5,7,8].…”
Section: Introductionmentioning
confidence: 99%
“…MRI/ultrasonography-fusion or in-bore MRI prostate biopsy (PBx) can be used for targeted biopsy [3][4][5]. The Prostate Imaging Reporting and Data System (PI-RADS) classification, which was introduced in 2012, provides a framework for standardized reporting of findings in mpMRI of the prostate and has quickly gained widespread acceptance [6,7].…”
Section: Introductionmentioning
confidence: 99%
“…The MRI-ultrasound fusion technique is currently an interesting compromise to reduce overdiagnosis without missing an aggressive cancer [3][4][5]12 . Still, the additional cost of the technique and the extra-operating time needed leave a place for conventional ultrasoundguided randomized biopsies, even in centers where both techniques are available.…”
Section: Discussionmentioning
confidence: 99%
“…Prostatic Multi-Parametric Magnetic Resonance Imaging (MRI) has proved helpful in selecting patients awaiting prostate biopsies by showing high Gleason score lesions [2][3][4][5][6] and allowing the performance of targeted biopsies using various techniques 7 .…”
Section: Introductionmentioning
confidence: 99%